ORGAN CREATION BY IOHANN SEBASTIAN BAX - Ikromova Farangis Yigitali qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article provides information about the life of the great German composer Iohann Sebastian Bax. The creative image of the artist is also reflected in the article.